ANALYSIS OF BREAST LESIONS IN PREGNANT WOMEN AT THE HOSPITAL DAS CLÍNICAS DE RIBEIRÃO PRETO - Borba, Jessica Maria Camargo; Tiezzi, Daniel Guimarães; Rodrigues, Tamara; Carmo, Raquel Moura do; Andrade, Jurandyr Moreira de (Mastology, 2020)
Introduction: Few publications have analyzed the diagnostic profile of nodules detected during pregnancy, but most lesions diagnosed in this stage are benign. Nevertheless, breast cancer is the most common malignant neoplasm in these patients, making the differential diagnosis even more challenging. Objectives: To analyze the prevalence of palpable breast lesions in pregnant women treated at the mastology department of the Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto (HCFMUSP-RP) from 1984 to 2011. Methodology: This is a retrospective cross-sectional study based on the review of medical records of patients treated at the mastology department of HCFMUSP-RP when the service was a regional reference center for breast nodule investigation. We included all pregnant women referred for palpable nodules and submitted to biopsy or excision of the lesion (51 cases). Results were compared with two control groups. The 102 controls were matched by age for each case with an allowable variation of ±1 year. Statistical analysis was performed using Pearson›s χ2 test. Results: The mean age of the patients was 27.7 years in the group of pregnant women and 26.8 years in the control group. The most prevalent lesion in the group of pregnant women was fibroadenoma (43%), followed by malignant breast neoplasms (31%). Malignant lesions were diagnosed in 35.2% of pregnant women with a mean age of 31.2 years, and invasive ductal carcinoma was the most frequent. In the control group, the most common lesions were fibroadenoma and benign phyllodes, corresponding to 65.7% of cases. Twelve malignant lesions were diagnosed in the control group: 11 ductal carcinomas (10.7% – mean age of 36.7 years) and 1 liposarcoma. Comparing the groups regarding the histological diagnosis shows that benign nodular lesions represent two-thirds of control cases and 43% of pregnant women. The frequency of breast cancer in the group of pregnant women was significantly higher than in the control group (p<0.005). Conclusion: Specific pregnancy and lactation lesions are uncommon. Benign nodules are the most diagnosed at this stage, but the frequency of malignancy among pregnant women is higher than in the non-pregnant group of com-parable age, and their mean age is lower. Therefore, nodules detected during pregnancy should be promptly investigated with imaging tests and biopsy.